Poverty relief or poverty eradication? (Acta Theologica)
The author challenges the reader to make two mindshifts: from a focus on poverty relief to an emphasis on poverty eradication; and from viewing the poor as the objects of poverty alleviation to accepting them as the subjects of poverty eradication. The case is argued and a practical approach towards poverty eradication is proposed.